A polymorph of the 6, 13-dichloropentacene organic semiconductor: crystal structure, semiconductor measurements and band structure calculations1. Issue 22 (14th June 2015) - Hatcher, Peggy V.; Reibenspies, Joseph H.; Haddon, Robert C.; Li, Dawen; Lopez, Nereo; Chi, Xiaoliu
<x xml:space="preserve">Abstract</x> A new polymorph of the 6, 13-dichloropentacene organic semiconductor was discovered, and its properties were compared with those of an earlier reported polymorph.